Ameliorative effects of pyrazinoic acid against oxidative and metabolic stress manifested in rats with dimethylhydrazine induced colonic carcinoma. Issue 5 (4th May 2017) - Sahdev, Anil K.; Raj, Vinit; Singh, Ashok K.; Rai, Amit; Keshari, Amit K.; De, Arnab; Samanta, Amalesh; Kumar, Umesh; Rawat, Atul; Kumar, Dinesh; Nath, Sneha; Prakash, Anand; et al.
ABSTRACT: Pyrazinoic acid (PA) is structurally similar to nicotinic acid which acts on G-protein-coupled receptor (GPR109A). GPR109A expresses in colonic and intestinal epithelial sites, and involves in DNA methylation and cellular apoptosis. Therefore, it may be assumed that PA has similar action like nicotinic acid and may be effective against colorectal carcinoma (CRC). CRC was produced via subcutaneous injection of dimethylhydrazine (DMH) at 40 mg/kg body weight once in a week for 4 weeks. After that, PA was administered orally at 2 doses of 10 and 25 mg/kg daily for 15 d to observe the antiproliferative effect. Various physiologic, oxidative stress, molecular parameters, histopathology, RT-PCR and NMR based metabolomics were performed to evaluate the antiproliferative potential of PA. Our results collectively suggested that PA reduced body weight, tumor volume and incidence no. to normal. It restored various oxidative stress parameters and normalized IL-2, IL-6, and COX-2 as compared with carcinogen control. In molecular level, overexpressed IL-6 and COX-2 genes became normal after PA administration. Again, normal tissue architecture was prominent after PA administration. Score plots of PLS-DA models exhibited that PA treated groups were significantly different from CRC group. We found that CRC rat sera have increased levels of acetate, glutamine, o-acetyl -glycoprotein, succinate, citrulline, choline, o-acetyl choline, tryptophan, glycerol, creatinine, lactate, citrate and decreased levels of 3-hydroxy butyrate, dimethyl amine, glucose, maltose, myoinositol. Further the PA therapy has ameliorated the CRC-induced metabolic alterations, signifying its antiproliferative properties. In conclusion, our study provided the evidence that PA demonstrated good antiproliferative effect on DMH induced CRC and thus demonstrated the potential of PA as a useful drug for future anticancer therapy.